Numerical Study of Non-Newtonian Fluid in a Cavity with Corrugated Bottom Wall Using Buongiorno’s Mathematical Model - Mawa, Hure Zannatul; Azad, Md. Abul Kalam; Alam, Chowdhury Sadid; Rahman, Md. Mustafizur (Trends in Sciences, 2022)
A 2-dimensional computational analysis is carried out for a time dependent double diffusive mixed convection flow using non-Newtonian nanofluid. A square-shaped cavity with a corrugated bottom wall is taken with higher temperature and concentration on the top wall. The physical model under consideration is represented by a set of governing equations and solved using the Galerkin weighted residual method based on Finite Element Analysis. Solutions are done for 4 controlling parameters such as Richardson number (Ri = 0.1 - 15), Lewis number (Le = 0.5 - 3), and thermophoresis parameter (Nt = 0.2 - 0.9), and Brownian motion parameter (Nb = 0.2 - 1.0) at different values of τ. For the aforementioned parameters, heat and mass transfer rates, temperature distributions, velocity distributions, and mass distributions in terms of isotherm, streamlines, and iso-concentration are graphically presented. It has been observed that for higher values of Ri, both Nuav and Shav increased while Le decreased for higher values of Nt at any fixed time. It is worth noting that the considered parameter exhibits consistent behavior after a while. HIGHLIGHTS The numerical analysis of non-Newtonian nanofluid with a corrugated bottom wall and a sliding upward wall is performed using Buongiorno's mathematical model The effect of the Richardson number, Lewis number, Brownian motion, and thermophoresis parameters on different dimensionless time periods is addressed The heat and mass transfer rate is increased as the Richardson number, Lewis number, Brownian motion, and thermophoresis parameters increase in value GRAPHICAL ABSTRACT